Preparation and Characterization of Muscone Oil-Based Cyclodextrin Metal–Organic Frameworks: Molecular Dynamics Simulations and Stability Evaluation - Zifan Qiao; Lihua Chen; Mubarak G. Bello; Shiyu Huang (Pharmaceutics)
Objective: Muscone (MUS), a primary active component of musk, is known for its significant pharmacological properties. However, its clinical application is limited due to poor water solubility and moderate stability. This study aims to address these limitations by encapsulating MUS within biodegradable γ-cyclodextrin metal–organic frameworks (γ-CD-MOFs) using a solvent-free method to enable oral MUS delivery by improving solubility and stability, pending in vivo validation. Methods: MUS was encapsulated into γ-CD-MOFs using a solvent-free method, achieving an optimal loading rate of 10.6 ± 0.7%. Comprehensive characterization was performed using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA). Biocompatibility was assessed using RAW264.7 cells, and molecular dynamics simulations were conducted to study the interactions between MUS and γ-CD-MOFs. Results: Characterization techniques confirmed the successful encapsulation of MUS into γ-CD-MOFs. Biocompatibility studies revealed no cytotoxicity, indicating that the system is safe for drug delivery. Molecular dynamics simulations showed that MUS preferentially occupies the large spherical cages of γ-CD-MOFs, driven by non-covalent interactions. Solubility tests and in vitro release studies demonstrated that the solubility of MUS was improved after encapsulation within γ-CD-MOFs. Stability assessments indicated that γ-CD-MOFs significantly enhanced the thermal and photostability of MUS, with high residual amounts remaining under various storage conditions. Conclusions: This study demonstrates the potential of γ-CD-MOFs to solidify MUS, enhance its solubility, and improve its storage stability, providing a foundation for its future use in pharmaceutical applications.